Risk Factors for Long-Term Mortality and Amputation after Open and Endovascular Treatment of Acute Limb Ischemia - Genovese, Elizabeth A (Ann Vasc Surg, 2015)
BACKGROUND: Acute limb ischemia (ALI) is a highly morbid and fatal vascular emergency with little known about contemporary, long-term patient outcomes. The goal was to determine predictors of long-term mortality and amputation following open and endovascular treatment of ALI. METHODS: A retrospective review of ALI patients at a single institution from 2005-2011 was performed to determine the impact of revascularization technique on 5-year mortality and amputation. For each main outcome two multivariable models were developed; the first adjusted for preoperative clinical presentation and procedure type, the second also adjusted for postoperative adverse events. RESULTS: Four hundred and forty-five limbs in 411 patients were treated for ALI. Interventions included surgical thrombectomy (48%), emergent bypass (18%), and endovascular revascularization (34%). Mean age was 68 ± 15 years, 54% were male, and 23% had cancer. The majority of patients presented with Rutherford Classification IIa (54%) or IIb (39%). The etiology of ALI included embolism (27%), in-situ thrombosis (28%), thrombosed bypass grafts (32%), and thrombosed stents (13%). Patients treated with open procedures had significantly more advanced ischemia and higher rates of post-operative respiratory failure, while patients undergoing endovascular interventions had higher rates of technical failure. Rates of post-procedural bleeding and cardiac events were similar between both treatments. Excluding Rutherford Class III patients (n=12), overall 5-year mortality was 54% (stratified by treatment, 65% for thrombectomy, 63% for bypass, and 36% for endovascular, p<.001); 5-year amputation was 28% (stratified by treatment, 18% for thrombectomy, 27% for bypass, and 17% for endovascular, p=0.042). Adjusting for comorbidities, patient presentation, adverse events and treatment method, the risk of mortality increased with age (HR=1.04, p<.001), female gender (HR=1.50, p=.031), cancer (HR=2.19, p<.001), fasciotomy (HR=1.69, p=.204) in-situ thrombosis or embolic etiology (HR=1.73, p=.007), cardiac adverse events (HR=2.25, p<.001), respiratory failure (HR=2.72, p<.001), renal failure (HR=4.70, p<.001) and hemorrhagic events (HR=2.25, p=.003). Risk of amputation increased with advanced ischemia (Rutherford IIb compared to IIa, HR=2.57, p<.001), thrombosed bypass etiology (HR=3.53,p=.002), open revascularization (HR=1.95,p=.022), and technical failure of primary intervention (HR=6.01, p<.001). CONCLUSIONS: Following the treatment of ALI, long-term mortality and amputation rates were greater in patients treated with open techniques; OR patients presented with a higher number of comorbidities and advanced ischemia, while also experiencing a higher rate of major postoperative complications. Overall, mortality rates remained high and were most strongly associated with baseline comorbidities, acuity of presentation, and perioperative adverse events, particularly respiratory failure. Comparatively, amputation risk was most highly associated with advanced ischemia, thrombosed bypass, and failure of the initial revascularization procedure.